2005
DOI: 10.1177/000331970505600109
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications of the Intra-aortic Balloon Counterpulsation

Abstract: From September 1994 to December 2002, 6,274 cardiosurgery operations were performed at the Department of Cardiac Surgery, University Hospital, Hradec Kralove, Czech Republic. Intra-aortic balloon counterpulsation (IABP) was applied in 192 cases (3.1%). From this group of 192 counterpulsated patients 103 were successfully treated (53.6%); 89 counterpulsated patients (46.4%) died from the surgical procedure (30-day mortality rate). In 5 cases (2.6%) from the group of 192, the IABP was introduced before the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In our study the rate of ischemic complications was 2.6% and the rate of minor bleeding complications was 4.2%. These findings are in accord with the complication rates of previous studies 5–11 . There was no difference concerning vascular complications in Group I (<24 hours following surgery) and Group II (>24 hours following surgery).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study the rate of ischemic complications was 2.6% and the rate of minor bleeding complications was 4.2%. These findings are in accord with the complication rates of previous studies 5–11 . There was no difference concerning vascular complications in Group I (<24 hours following surgery) and Group II (>24 hours following surgery).…”
Section: Discussionsupporting
confidence: 92%
“…The meta‐analysis of Dyub et al 4 reported a 3.7% rate of either limb ischemia or hematoma after cardiac surgery. In other studies 5–7 the rate of ischemic complications after cardiac surgery varied from 1.08% to 5.7%. It should be noted that no anticoagulation protocol is described in any of these publications.…”
Section: Discussionmentioning
confidence: 88%
“…[16] Aortic dissection occurs in about 1% of cases of IABP insertion. [1819] This is recognized on contrast-enhanced CT by the presence of a low-attenuation linear flap with the IABP positioned within the false lumen [Figure 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common complications include vascular injury, limb ischemia and infection. Other possible events include dissection or rupture of the aorta, due to balloon rupture, occurrence of clots or emboli or atheroma plaques, hemorrhages, a thrombocytopenia, besides cases of paraplegia, after IABP use (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Republic reports that complications occur in 11.5% of patients, with limb ischemia as the most frequent (5.7%) (3) . A retrospective European study that involved 911 patients identified incidence levels of IABP-related vascular complications ranging between 8.7 and 20%.…”
Section: Introductionmentioning
confidence: 99%